2017
DOI: 10.1186/s40900-017-0055-1
|View full text |Cite
|
Sign up to set email alerts
|

The consultation of rugby players in co-developing a player health study: feasibility and consequences of sports participants as research partners

Abstract: Plain English summary Many funding bodies within the United Kingdom and globally have encouraged public involvement in research. The Department of Health has also called public involvement a sign of good research. Despite the wide acceptance of public involvement improving many aspects of research, from its design to its communication, involvement has varied levels of implementation across different fields of research. Sports people have rarely been involved in research, partly as this research tends not to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…The effectiveness of consulting rugby players (as research partners in the university environment/colleagues) was demonstrated in a previous study [54]. They made an important contribution to the construction of a questionnaire aimed at assessing their health, noting superior involvement, additions and improvements for standardized items or those with free answers, and suggestions about their own experiences, similar issues also encountered in our study.…”
Section: Discussionsupporting
confidence: 72%
“…The effectiveness of consulting rugby players (as research partners in the university environment/colleagues) was demonstrated in a previous study [54]. They made an important contribution to the construction of a questionnaire aimed at assessing their health, noting superior involvement, additions and improvements for standardized items or those with free answers, and suggestions about their own experiences, similar issues also encountered in our study.…”
Section: Discussionsupporting
confidence: 72%
“…Six PPI sessions were held, resulting in consensus on the cricket-specific variables and wellbeing measures and the phrasing for capturing these variables, as described in other PPI practice. 17 Three wellbeing measures stated, “Considering the benefits and risks of my previous participation in cricket, I would do the same again,” “Considering the benefits and risks of my previous participation in cricket, I would recommend this to my children, relatives, or close friends,” and “Did your cricket career enrich your life?” The responses of each wellbeing measure were categorised into “agree”, “undecided”, and “disagree” responses.…”
Section: Methodsmentioning
confidence: 99%
“…Patient and public involvement was undertaken throughout the research cycle of this study, with rugby players assisting as consultants co-developing and managing this study 20 . Current and former players were extensively involved throughout the research cycle, with study and questionnaire design, study oversight, and questionnaire testing.…”
Section: Methodsmentioning
confidence: 99%
“…This process aimed to ensure the questionnaire was accessible and intuitive for players, and that it was revised and tested with the target population. Two player involvement fora were undertaken with eleven players informing the recruitment strategy, research agenda and functionality of online data collection, the process and output of which have been reported elsewhere 20 .…”
Section: Methodsmentioning
confidence: 99%